REPRESENTASI BADUT PADA KARYA SENILUKIS BUDI “UBRUX” HARYONO - Harun, Hamdan; Adisukma, Wisnu (Texture: Visual Art and Culture Journal, 2024)
The process of creating Budi'spainting"Ubrux"emphasizes that social reality is the main basis for the inspiration for its creation.Direct involvement with social,political and cultural issues is reflected in the themes raised in his work, such as the figure of the clown which is used as a critique of the abuse of power by government officials. This research uses a descriptive qualitative approach with in-depth interview methods, observation and document analysis. The analysis was carried out by applying StuartHall's theory of representation,especially the encoding and decoding approach, to understand how the meaning in Budi's work "Ubrux" is produced and received by the audience.This study reveals the complexity of visual messages through symbols such as clown faces,haircolor,and facial expressions.The representational analysis approach makes it possible to explore the symbolic meaning and social context in these works,enriching our understanding of the social,political and cultural criticism conveyed by Budi "Ubrux" through the clown theme